Characterization of a p53/miR-34a/CSF1R/STAT3 Feedback Loop in Colorectal CancerSummary - Xiaolong Shi; Markus Kaller; Matjaz Rokavec; Thomas Kirchner; David Horst; Heiko Hermeking (Cellular and Molecular Gastroenterology and Hepatology, 2020)
Background & Aims: The miR-34a gene is a direct target of p53 and is commonly silenced in colorectal cancer (CRC). Here we identified the receptor tyrosine kinase CSF1R as a direct miR-34a target and characterized CSF1R as an effector of p53/miR-34a-mediated CRC suppression. Methods: Analyses of TCGA-COAD and three other CRC cohorts for association of mRNA expression and signatures with patient survival and molecular subtypes. Bioinformatics identification and experimental validation of miRNA and transcription factor targets. Functional analysis of factors/pathways in the regulation of epithelial-mesenchymal transition (EMT), invasion, migration, acquired chemo-resistance and metastasis. Analyses of protein expression and CpG methylation within primary human colon cancer samples. Results: In primary CRCs increased CSF1R, CSF1 and IL34 expression was associated with poor patient survival and a mesenchymal-like subtype. CSF1R displayed an inverse correlation with miR-34a expression. This was explained by direct inhibition of CSF1R by miR-34a. Furthermore, p53 repressed CSF1R via inducing miR-34a, whereas SNAIL induced CSF1R both directly and indirectly via repressing miR-34a in a coherent feed-forward loop. Activation of CSF1R induced EMT, migration, invasion and metastasis of CRC cells via STAT3-mediated down-regulation of miR-34a. 5-FU resistance of CRC cells was mediated by CpG-methylation of miR-34a and the resulting elevated expression of CSF1R. In primary CRCs elevated expression of CSF1R was detected at the tumor invasion front and was associated with CpG methylation of the miR-34a promoter as well as distant metastasis. Conclusions: The reciprocal inhibition between miR-34a and CSF1R and its loss in tumor cells may be relevant for therapeutic and prognostic approaches towards CRC management.